The Kinetic Compensation Effect In The Decomposition Of Calcium Carbonate - Harbbi, K. H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Some specific factors that cause the kinetic compensation effect during the decomposition CaC03 are identified. The role of the C02 equilibrium pressure is examined in relation to the kinetic compensation effect. This investigation also shows why non - iso thermal experiments have some time necessarily to yield value of activation energy different from the value obtained from isothermal experiments.